The changes in fractal dimension after a maximal exertion in swimming - Barbosa, T. M.; Simin, C.; Forte, P.; Morais, J. E. (2016 1st International Conference on Technology and Innovation in Sports, Health and Wellbeing (TISHW), 2016)
Quite often linear variables are not sensitive enough to explain the changes in the motor behavior of elite athletes. So, non-linear variables should be selected. The aim was to compare the fractal dimension before and after a maximal bout swimming front-crawl. Twenty-four subjects performed an all-out 100m trial swimming front-crawl. Immediately before (Pre-test) and after the trial (Post-test) a speed-meter cable was attached to the swimmer's waist to measure the hip speed from which fractal dimension was derived. The fractal dimension showed a significant decrease with a moderate effect size between pre- and post-tests. Twenty-one out of 24 swimmers decreased the fractal dimension. As a conclusion, there is a decrease in the fractal dimension and hence in the swimming behavior complexity being under fatigue after a maximal trial.